2009
DOI: 10.1128/aac.00985-09
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Profile of Tigecycline against Methicillin-Resistant Staphylococcus aureus in an Experimental Pneumonia Model

Abstract: Tigecycline (TGC) is an extended-spectrum antibiotic with activity against Staphylococcus aureus, including methicillin (meticillin)-resistant S. aureus strains, which are well-recognized pathogens in nosocomial pneumonia. The objective of this study was to characterize the exposure-response relationship for TGC against S. aureus in an immunocompromised BALB/c murine pneumonia model. Six S. aureus isolates were studied, and the TGC MICs for those isolates ranged from 0.125 to 0.5 mg/liter. The pharmacokinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 17 publications
4
25
0
Order By: Relevance
“…Utilizing four S. pneumoniae strains in a murine neutropenic thigh model, Christianson et al demonstrated that a 24-h free-drug AUC/MIC target of 24 for doxycycline was associated with net stasis and that a value of 120 was associated with a 2-log 10 kill (17). Tigecycline PK/PD studies have also demonstrated the importance of AUC/MIC as the PK/PD driver of efficacy with net stasis targets that have ranged from 2 to 5 for a variety of pathogens (18)(19)(20). The AUC/MIC exposures associated with efficacy in the current preclinical model for omadacycline are similar to other tetracycline class antibiotic PK/PD studies.…”
Section: Figsupporting
confidence: 55%
“…Utilizing four S. pneumoniae strains in a murine neutropenic thigh model, Christianson et al demonstrated that a 24-h free-drug AUC/MIC target of 24 for doxycycline was associated with net stasis and that a value of 120 was associated with a 2-log 10 kill (17). Tigecycline PK/PD studies have also demonstrated the importance of AUC/MIC as the PK/PD driver of efficacy with net stasis targets that have ranged from 2 to 5 for a variety of pathogens (18)(19)(20). The AUC/MIC exposures associated with efficacy in the current preclinical model for omadacycline are similar to other tetracycline class antibiotic PK/PD studies.…”
Section: Figsupporting
confidence: 55%
“…Animals were maintained and used in accordance with National Research Council recommendations and were provided food and water ad libitum. The murine lung infection model used in this analysis has been described previously (16,19). Briefly, mice were rendered neutropenic by intraperitoneal injections with 100 and 250 mg/kg of body weight of cyclophosphamide (Cytoxan; BristolMyers Squibb, Princeton, NJ) given 1 and 4 days prior to inoculation, respectively.…”
Section: Antimicrobialsmentioning
confidence: 99%
“…Similar targets in our model were not calculated, as only three of six isolates achieved such a response. The inability to reach a 2 log 10 CFU reduction has been encountered among other currently available bactericidal and bacteriostatic anti-MRSA antimicrobials in the neutropenic and immunocompetent in vivo lung infection model (18,(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%